Chemoautotrophic microbial mantle prevalence in Murra El Elevyn: catastrophic decline or seasonal fluctuation? - Buzzacott, Peter; Buckley, Dene; Waterworth, Pippa (2010)
The Nullarbor Plain of Western Australia is a plateau of horizontal Eocene and Miocene karst, home to numerous extensive caves flooded with brackish water. In 1999 chemoautotrophic microbial mantles were recorded in Murra El Elevyn, and samples collected in Weebubbie and Warbla caves. The temperature in Murra El Elevyn was 23.7 degrees Celsius, and in nearby Tommy Graham’s cave it was 23.1 degrees. One year later return visits were made to Weebubbie and Warbla caves, and divers reported limited re-growth of 1-2cm where samples had previously been collected. In September 2009 microbial mantles were again recorded in abundance in Murra El Elevyn cave, hanging 20-30cm long underneath ledges and covering the rubble below. The temperature was recorded to have fallen to 18.9C. On a return visit six months later, after the dry Australian summer, divers found substantially fewer mantles, the largest of which was a mere 2cm long. Water temperature was 19.3C in Murra El Elevyn and 23.4C in Tommy Graham’s cave. Meanwhile, the mantles at Weebubbie and nearby Olgolwin caves remained abundant. Given the rapid decline over six months in the prevalence of microbial mantles in Murra El Elevyn alone, we postulate two potential scenarios. Firstly, that localised falling average water temperature has transformed Murra El Elevyn into an inhospitable environment (e.g. altered water chemistry), causing the catastrophic demise of microbial mantles in that cave. Alternately, with notably different rain-driven dissolved nutrient ingress to Weebubbie and Warbla caves, the otherwise morphologically similar mantles in Murra El Elevyn have evolved an annual, seasonally regulated lifecycle and are, thus, relatively faster growing than has been observed in other Nullarbor caves. Further research is underway to monitor this previously unreported phenomena and to establish which, if either of these possibilities, is likelier the cause.